EMPLOYEE GREEN BEHAVIOUR (EGB) AT WORK: THE MODERATING EFFECTS OF ISLAMIC VALUES - Bashirun, Siti Norashikin; Abdul Rahman, Afrah Hayati; Mohd Razali, Masliza; Lagiman, Norizam (Jurnal ’Ulwan, 2020)
Environmental sustainability issues are one of the major concerns to be addressed by many organizations. As one of the options is by encouraging pro-environmental or green behavior at workplace which could result to an employee responsibility towards reducing environmental problems. Similarly, Islamic thought also emphasized on the importance of protecting the environment and preserving nature. In fact, elements found in green practices are coherent with the explanation of Allah in the Quran. Nevertheless, the Muslim is less aware of the relationship between environmental behavior and Islam. Hence, this concept paper is to examine employee green behavior (EGB) from the Islamic perspectives. This study will provide insights for further research on environmental sustainability and benefits organizations that are interested in encouraging such behaviour with regards of Islamic practice. Although, the study is conceptual in nature, its findings could be used as the foundation for future research in order to identify the most significant Islamic values that influence green behaviour implementations